Abaloparatide increases bone mineral density and bone strength in ovariectomized rabbits with glucocorticoid-induced osteopenia - Chandler, H. (Osteoporos Int, 2019)
SUMMARY: Glucorticoid (GC) therapy is the commonest cause of secondary osteoporosis. Ovariectomized rabbits receiving the GC methylprednisolone for 6 weeks exhibited relatively lower vertebral and femoral bone mass. Treatment with the PTH receptor agonist abaloparatide for 12 weeks during ongoing methylprednisolone administration increased cortical and trabecular bone mass and femur bending strength. INTRODUCTION: Abaloparatide, an osteoanabolic PTHrP analog, increases bone mineral density (BMD) and reduces fracture risk in women with postmenopausal osteoporosis. This study assessed abaloparatide effects on BMD and bone strength in ovariectomized (OVX) rabbits with glucocorticoid (GC)-induced osteopenia. METHODS: Thirty-two rabbits underwent OVX and 8 underwent sham surgery. One day later, 24 OVX rabbits began daily s.c. GC injections (methylprednisolone, 1 mg/kg/day) for 6 weeks, while 8 OVX and 8 sham controls received no GC. GC-challenged rabbits (8/group) then received GC (0.5 mg/kg/day) along with daily s.c. vehicle (GC-OVX), abaloparatide 5 μg/kg/day (ABL5), or 25 μg/kg/day (ABL25) for 12 weeks, and the no-GC OVX and sham controls received daily vehicle. RESULTS: GC-OVX rabbits showed significant deficits in vertebral and proximal femur areal BMD, lower cortical area, thickness and volumetric BMD of the femur diaphysis, and reduced trabecular bone volume and volumetric BMD in the vertebra and distal femur versus sham controls. These deficits were significantly reversed in the ABL25 group, which also showed enhanced trabecular micro-architecture versus GC-OVX controls. Destructive bending tests showed significantly lower femur diaphysis ultimate load and bending rigidity of the femoral diaphysis in the GC-OVX group versus sham controls, whereas these parameters were similar in the ABL25 group vs sham controls. CONCLUSIONS: Abaloparatide 25 μg/kg/day mitigated the adverse effects of GC administration on cortical and trabecular bone and improved femoral strength in OVX rabbits. These results suggest potential promise for abaloparatide as an investigational therapy for glucocorticoid-induced osteoporosis.